2013
DOI: 10.1037/a0030165
|View full text |Cite
|
Sign up to set email alerts
|

A mediation model of the relationship of cultural variables to internalizing and externalizing problem behavior among Cambodian American youth.

Abstract: This study examined a mediation model of the relationship of acculturation (Anglo/White cultural orientation) and enculturation (Cambodian cultural orientation) to internalizing and externalizing problem behavior among 191 Cambodian American high school students from an urban school district in the Northeast region of the United States. The hypothesized mediators were parent–child acculturation gap and school attachment. The results partially supported the hypothesized mediation model, indicating that parent–c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…Empirical research with Asian American children and youth that is designed to examine biculturalism (Sirikantraporn, ), acculturation and enculturation (Dinh, Weinstein, Tein, & Roosa, ), and bicultural integration (Huynh, Nguyen, & Benet‐Martinez, ) illustrates the centrality of interpretive processes in development as Asian American youth navigate, integrate, fuse, hybridize, mute, or otherwise transform multiple selves to create coherence. Furthermore, the relevance of these organizing and meaning‐making processes to developmental outcomes is examined in different areas of psychological adjustment among specific Asian ethnic groups.…”
Section: Culture As Meaning Making In Developmental Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research with Asian American children and youth that is designed to examine biculturalism (Sirikantraporn, ), acculturation and enculturation (Dinh, Weinstein, Tein, & Roosa, ), and bicultural integration (Huynh, Nguyen, & Benet‐Martinez, ) illustrates the centrality of interpretive processes in development as Asian American youth navigate, integrate, fuse, hybridize, mute, or otherwise transform multiple selves to create coherence. Furthermore, the relevance of these organizing and meaning‐making processes to developmental outcomes is examined in different areas of psychological adjustment among specific Asian ethnic groups.…”
Section: Culture As Meaning Making In Developmental Processesmentioning
confidence: 99%
“…For example, in examining the relation of acculturation and enculturation with externalizing and internalizing behaviors in school, Dinh et al. () found that the parent–child acculturation gap mediated the relationship for internalizing but not for externalizing problem behaviors among youth of Cambodian descent in the United States. Youth who maintained a Cambodian orientation perceived less of an acculturation gap with their parents and were less likely to report internalizing behaviors such as depression.…”
Section: Culture As Meaning Making In Developmental Processesmentioning
confidence: 99%
“…The process of adaptation to mainstream U.S. culture typically differed between parents and children, particularly the 1.5 and 2 nd generation (U.S.-born) children, leading to potential intergenerational cultural conflicts and dissatisfaction in the parent-child relationship (Dinh & Nguyen, 2006;Xiong, Detzner, & Cleveland, 2004-05;Zhou, 2001). Parents tended to maintain core aspects of traditional cultural and family values while their children tended to adopt more mainstream U.S. values, behaviors, and lifestyles (Dinh, Sarason, & Sarason, 1994;Dinh et al, 2013;McCabe & Dinh, 2018). The extent of differential patterns in adaptation is partly influenced by the extent of differences in age and generational status.…”
Section: Parent-child Relationshipmentioning
confidence: 99%
“…The 2010 ACS also showed that for family poverty status, 13% of Vietnamese, 12.2% of Laotian, 27.4% of Hmong, and 18.2% of Cambodian families were living at or below the poverty level, as compared to 11.3% and 9.3%, respectively, for the total U.S. population and total Asian Pacific Islander population. These census data, 20 years apart, indicated remarkable progress and resilience among SEAs while highlighting the continuing socioeconomic challenges, especially for the Hmong and Cambodian groups, which may have both positive and negative long-term consequences for individual and family well-being (e.g., Dinh, Weinstein, Tein, & Roosa, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In ethnic identity research, for example, adolescents are influenced not only by the ways others define them but also by their own interpretations (Kiang & Fuligni, ; Kiang & Luu, ). Moreover, ethnic identity is not simply a developmental outcome; rather, it is a process by which children and adolescents organize their sense of selves and make meaning of their ethnic socialization and discrimination experiences (Dinh, Weinstein, Tein, & Roosa, ; Greene, Way, & Pahl, ; Sirikantraporn, ).…”
Section: The Special Sectionmentioning
confidence: 99%